Metatranscriptomic Assessment of the Microbial Community Associated With the Flavescence dorée Phytoplasma Insect Vector Scaphoideus titanus - Abbà, Simona; Rossi, Marika; Vallino, Marta; Galetto, Luciana; Marzachì, Cristina; Turina, Massimo (Frontiers in Microbiology, 2022)
Phytoplasmas are insect-borne pathogenic bacteria that cause major economic losses to several crops worldwide. The dynamic microbial community associated with insect vectors influence several aspects of their biology, including their vector competence for pathogens. Unraveling the diversity of the microbiome of phytoplasma insect vectors is gaining increasing importance in the quest to develop novel microbe-based pest control strategies that can minimize the use of insecticides for a better environmental quality. The leafhopper Scaphoideus titanus is the primary vector of Flavescence dorée phytoplasma, a quarantine pest which is dramatically affecting the main grape‐growing European countries. In this study, RNA-Seq data, which were previously used for insect virus discovery, were further explored to assess the composition of the whole microbial community associated with insects caught in the wild in both its native (the United States) and invasive (Europe) areas. The first de novo assembly of the insect transcriptome was used to filtering the host sequencing reads. The remaining ones were assembled into contigs and analyzed by blastx to provide the taxonomic identification of the microorganisms associated with S. titanus, including the non-bacterial components. By comparing the transcriptomic libraries, we could differentiate the stable and consistent associations from the more ephemeral and flexible ones. Two species appeared to be universal to the core microbiome of S. titanus: the obligate bacterial symbiont Candidatus Sulcia muelleri and an Ophiocordyceps-allied fungus distantly related to yeast-like symbionts described from other hemipterans. Bacteria of the genus Cardinium have been identified as another dominant member of the microbiome, but only in the European specimens. Although we are yet to witness how the interplay among microorganisms influences the vector competence of S. titanus, this unbiased in silico characterization of its microbiome is paramount for identifying naturally occurring targets for new biocontrol strategies to counteract Flavescence dorée spread in Europe.